Polarized electroluminescence of a discotic mesogenic compound - Benning, Stephan A.; Oesterhaus, Reinhold; Kitzerow, Heinz-Siegfried (Liquid Crystals)
Keywords: Condensed Matter Physics; General Materials Science; General Chemistry

‚An der Spitze der musikalischen Bewegung‘ – Die Reisen der Bilse’schen Kapelle - Grotjahn, Rebecca (Mitteilungen der Benjamin Bilse Gesellschaft)

Koketterie und Wahnsinn – zur Weiblichkeit des Koloraturgesangs - Grotjahn, Rebecca (Oper aktuell. Bd. XXVII: Die Bayerische Staatsoper 2004/05. Anlässlich der Münchner Opern-Festspiele 2004)

An adaptive channel tracking method for MIMO-OFDM systems - Tong, Jun; Gong, Yaohuan; Sun, Shengxian (Int.\ Conf.\ Comm.\ Circuits Syst.)
The tracking of the time-varying channel is crucial for MIMO-OFDM wireless communication systems. Aiming at doubly-selective fading MIMO channels, we present a novel pilot pattern and the corresponding adaptive channel tracking algorithm. Compared with the traditional pilot patterns, the new pattern has higher frequency efficiency and is more suitable for large transmit arrays. The computational complexity, frequency efficiency and BER performance of the system assisted by the proposed channel tracking scheme are analyzed. Simulation results demonstrate that the proposed scheme can track the timevarying channel effectively.

Polyspectra of analytic signals - Schreier, Peter J.; Scharf, Louis L. (Proc.\ IEEE Int.\ Conf.\ Acoustics, Speech and Signal Process.)
For complex signals, n-th order moment functions can be defined in 2n different ways, depending on the placement of complex conjugates. We demonstrate that, for stationary analytic signals, only a few of these different moments are actually required for a complete n-th order description. Which, and how many of them, depends on the signal’s spectrum. We investigate properties of n-th order moments and spectra with different conjugation patterns and show how they provide different information about the signal.

Confined phonons in glasses - A study by nuclear inelastic absorption and Raman scattering - Asthalter, T.; Bauer, Matthias; van Bürck, U.; Sergueev, I.; Franz, H.; Chumakov, A.I. (The European Physical Journal E)
Keywords: Surfaces and Interfaces; General Materials Science; General Chemistry; Biophysics; Biotechnology

Luise Adolpha Le Beau (1850-1927): Die Symphonische Dichtung „Hohen-Baden“ - Tumat, Antje (Klangwelten: Lebenswelten – Komponistinnen in Südwestdeutschland)

Surface modification of epoxy-functionalized acrylate colloids - Kramer, Thomas; Röder, Thorsten; Huber, Klaus; Kitzerow, Heinz-Siegfried (Polymers for Advanced Technologies)
Keywords: Polymers and Plastics

Colloid–polymer mixtures in solution with refractive index matched acrylate colloids - Kramer, Thomas; Scholz, Stephanie; Maskos, Michael; Huber, Klaus (Journal of Colloid and Interface Science)
Keywords: Colloid and Surface Chemistry; Surfaces; Coatings and Films; Biomaterials; Electronic; Optical and Magnetic Materials

Particle scattering factor of pearl necklace chains - Schweins, Ralf; Huber, Klaus (Macromolecular Symposia)
Keywords: Materials Chemistry; Polymers and Plastics; Organic Chemistry; Condensed Matter Physics

Conformation and Phase Diagrams of Flexible Polyelectrolytes - Huber, Klaus; Volk, N.; Vollmer, D.; Schmidt, Manfred; Oppermann, W. (Polyelectrolytes with Defined Molecular Architecture II)

Surface modification of epoxy-functionalized acrylate colloids - Kramer, Thomas; Röder, Thorsten; Huber, Klaus; Kitzerow, Heinz-Siegfried (Polymers for Advanced Technologies)
Keywords: Polymers and Plastics

Niccolò Piccinni: La buona figliuola - Tumat, Antje (Hofoper in Schwetzingen. Musik – Bühnenkunst – Architektur)

Niccolò Piccinni: Gli stravaganti - Tumat, Antje (Hofoper in Schwetzingen. Musik – Bühnenkunst – Architektur)

Barbara Strozzi (1619-1677) - Tumat, Antje (Musikvermittlung und Genderforschung. Musikerinnen-Lexikon und multimediale Präsentationen)

Christoph Willibald Gluck: Alceste - Tumat, Antje (Hofoper in Schwetzingen. Musik – Bühnenkunst – Architektur)

Anton Schweitzer: Alceste - Tumat, Antje (Hofoper in Schwetzingen. Musik – Bühnenkunst – Architektur)

Maßstab Beethoven? Komponistinnen im Schatten des Geniekults. Hg. von Bettina Brand und Martina Helmig - Tumat, Antje (Die Musikforschung)

Science as a Self-Organizing Meta-Information System - Fuchs, Christian (Science of Self-Organization and Self-Organization of Science)

The Political System as a Self-Organizing Information System - Fuchs, Christian (Cybernetics and Systems 2004)